Toolbox of Theory and Understanding of Political Concepts - Ali Ashraf Nazari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Theory is considered an “approach” as a toolbox for constructing and experimentally examining questions and concepts. In recent decades, the debate over the status of theory has always been the subject of debate and intellectual debate. What is the essence of the theory? How can theory be considered as a more comprehensive toolbox for intervening in contemporary cultures, and what can be done about it? The focus of discussion, critique, and evaluation in this article is the book Theory Toolbox: Basic Concepts in Humanities, Social Sciences, and Art. The main idea of ​​the book is that, according to Gilles Deleuze, theory should be considered as a toolbox for constructing and experimenting with questions and concepts and as a more comprehensive tool for intervening in contemporary cultures. The book was written by Jeffrey Nealon and Susan Giroux and published in English in 2012 by Rowman & Little field. This book was translated into Persian in 1396 (2016) by Abbas Lotfizadeh and Morteza Khoshamadi and has been made available to those interested by Qoqnoos Publishing.